Iš žodžių kilmės aiškinimų - Karaliūnas, Simas (Baltistica, 1978)
On the origin of some words Lith. dial. apuokas “hair below, down” is said to be cognate either with Latv. apakša “bottom” (<*apak-tjā) or apukša “id.” (<*apuk-tjā) and apauška “id.” (←*apauk-tjā). *apa and *apu in *apak- and *apuk- are identified with IE adverbs-prepositions *apo and dial. *apu and -k- is thought of to be an (emphatic ?) particle. It is also assumed that the word apuokas was used to name an eagle owl after its rich feathers and consequently Pr. aukis “griffin” has nothing to do with the Lith. word. Lith. kéikti (-ia) “to scold, rail, call names” is being connected, on the one hand, with Lith. kykà “cursing, swearing, abuse”, kỹkastės, kỹkšena “discord, dissension, quarrel”, kỹkti (-ia) “to be ailing, to be sickly; to live hard, in penury...” etc. and, on the other, with Lith. kaĩkti (-ia) “to howl, squeak”, Serb.-Cr. čič “hard frost” (*keiki̯o-), Rus. чи́чер, чи́чера “sharp cold wind with rain in autumn etc.”. The author believes that Pr. ep-kieckan “vice” represents quite a different root, namely *kek- in Lith. kèkotis (-ojasi) “to quarrel, abuse one another”, keknóti (-ója) “to chuckle, giggle; to bark...”, kė̃kti (-ia) “to take pains, to labour; to live hard, in penury…” etc.